Cost Sharing under Uncertainty: An Algorithmic Approach to Cooperative Interval-Valued Games - Alf Kimms; Julia Drechsel (BuR - Business Research, 2009)
Recently, Branzei, Dimitrov, and Tijs (2003) introduced cooperative interval-valued games. Among other insights, the notion of an interval core has been coined and proposed as a solution concept for interval-valued games. In this paper we will present a general mathematical programming algorithm which can be applied to find an element in the interval core. As an example, we discuss lot sizing with uncertain demand to provide an application for interval-valued games and to demonstrate how interval core elements can be computed. Also, we reveal that pitfalls exist if interval core elements are computed in a straightforward manner by considering the interval borders separately.
urn:nbn:de:0009-20-21721
Keywords: 650; cooperative game theory; core; interval-valued games; lot-sizing; mathematical programming; Kooperatives Spiel; Core; Mathematische Optimierung; Algorithmus; Losgröße